Complementary Feeding Practices and Household Food Insecurity Status of Children Aged 6-23 Months in Shashemene City West Arsi Zone, Oromia, Ethiopia - Junayde Abdurahmen Ahmed; Kebede Kumsa Sadeta; Kelil Hussen Lembo (Hindawi Limited, 2022)
Introduction. Appropriate infant feeding practices are critical to a child's growth, health, and development during the first 1000 days of life. One in every six children worldwide receives a minimum acceptable diet. According to the EDHS 2016, the status of the minimum acceptable diet was 7 percent among children aged 6-23 months in Ethiopia. The study sought to ascertain the relationship between complementary feeding (CF) indicators and household food insecurity in children aged 6-23 months. Methods. A systematic sampling method was used to conduct a cross-sectional study of 536 mother-child pairs aged 6-23 months. The 24-hour dietary recall was used to collect data on CF practices using face-to-face interviews with socioeconomic and food security questionnaires. The relationship between complementary feeding indicators and household food insecurity was investigated using logistic regression analysis. The relationship between independent variables and complementary feeding indicators was determined using multivariate logistic regression. Results. Overall, a total of 67.9% of children received timely introduction of CF and Minimum Meal Frequency (MMF), Minimum Dietary Diversity (MDD), and Minimum Acceptable Diet were met by 61.7%, 42.5%, and 41.7%, respectively. Result of multivariate logistic regression showed there is significant association between household food security with MMF, MDD, and MAD [AOR: 2.02, 95% CI: (1.25-3.24); AOR: 1.55, 95% CI: (1.02-2.36); and AOR: 1.62, 9595% CI: (1.06-2.47)], respectively, while there was no association with introduction of CF [AOR = 0.87, 95% CI: (0.55-1.39)]. Conclusion. This study revealed that the rates of MMF, MDD, and MAD remained low in this study setting. Household socioeconomic status (wealth index, food security status, household income) and child age were found to be among the factors statistically significantly associated with complementary feeding practices indicators.